Islamic Financial Literacy and Its Influence on Student Financial Investment and Behavior - Fitriana Rahman; Laily Dwi Arsyianti (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2021)
Abstract. The Financial Services Authority survey 2019 shows an Islamic financial literacy rate of 8.93% and has not been evenly distributed in every sector, especially in the capital market. The capital market Islamic financial inclusion index also has the lowest among other sectors. This study aims to analyze the level of Islamic financial literacy of students of the FEM IPB University and its influence on investment decisions through financial behavior with descriptive analysis and SEM-PLS methods. The results show the average level of Islamic financial literacy of respondents is 81.17%. Islamic financial literacy influences investment decisions and financial behavior. Then, financial behavior directly influences investment decisions. It also mediates the influence of Islamic financial literacy on investment decisions. The other finding indicates that gender has no influence, while income has a positive and significant effect on investment decisions.Keywords: Financial Behavior, Investment Decision, Islamic Financial Literacy, SEM-PLS Abstrak. Survei Otoritas Jasa Keuangan 2019 menunjukkan tingkat literasi keuangan syariah sebesar 8,93% dan belum merata di setiap sektornya terutama pada pasar modal. Indeks inklusi keuangan syariah pasar modal juga memiliki nilai terendah di antara sektor lain. Penelitian ini bertujuan menganalisis tingkat literasi keuangan syariah mahasiswa FEM IPB University dan pengaruhnya terhadap keputusan investasi melalui perilaku keuangan dengan metode analisis deskriptif dan SEM-PLS. Hasil penelitian menunjukkan rata-rata tingkat literasi keuangan syariah responden adalah 81,17%. Literasi keuangan syariah berpengaruh terhadap keputusan investasi dan perilaku keuangan, kemudian perilaku keuangan berpengaruh langsung terhadap keputusan investasi dan mampu memediasi pengaruh literasi keuangan syariah terhadap keputusan investasi. Ditemukan pula bahwa jenis kelamin tidak memiliki pengaruh, sementara pendapatan berpengaruh positif dan signifikan terhadap keputusan investasi.Kata kunci: Literasi Keuangan Syariah, Keputusan Investasi, Perilaku Keuangan, SEM-PLS